Analisis Yuridis Sengketa Kepemilikan Tanah Waris antara Ahli Waris dan Pihak yang Menguasai Tanpa Alas Hak: Studi Putusan Mahkamah Agung Nomor 1229 PK/Pdt/2024 - Andrea Sakavino; hasim purba; Rosnidar Sembiring (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
Inheritance land ownership disputes between heirs and parties possessing land without legal title constitute an agrarian legal issue that affects legal certainty in Indonesia. This normative juridical study examines the legal standing of heirs, the legal consequences of unlawful possession and the application of law in Supreme Court Decision Number 1229 PK/Pdt/2024. The results indicate that ownership rights transfer automatically to heirs upon the death of the decedent, unlawful possession constitutes a tort under Article 1365 of the Civil Code and although the Court protects heirs’ rights, its reasoning still shows weaknesses regarding separate property status, absolute jurisdiction and the position of banking institutions.